ANALYSIS OF FACTORS AFFECTING VILLAGE TREASURER TAX COMPLIANCE IN BATU CITY - Hendi Subandi; Mohamad Irvanuddin Ibnu Fadhil (Universitas Airlangga, 2018)
The task of the village treasurer is to regulate and manage village finances, including the taxation aspect. However, the lack of tax knowledge and the quality of the Village Treasurer's human resources are a separate problem for the Village Treasurer's tax compliance. This study aims to analyze the factors that affect the tax compliance of the Village Treasurer in Batu City. The research instrument used was a questionnaire. Research respondents were all Village Treasurers in Batu City. The dependent variable in this study is the Village Treasurer's tax compliance while the independent variables are tax knowledge, tax services and tax sanctions. The entire population is used as a sample, which is 38 respondents. The validity test uses total correlation, while the reliability test uses Cronbach alpha. Classical assumption test includes normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing in this study uses simple regression analysis and multiple regression analysis. The results of this study indicate that there is a positive and significant influence between tax knowledge, tax services and tax sanctions on tax compliance from the Village Treasurer in Batu City.